O4.06 ANALYSIS OF RAF PROTEINS IN MALIGNANT GLIOMAS - Hagemann, C. (Oxford University Press, 2014)
OBJECTIVE: Low grade astrocytoma WHO grade II (LGA) display an increased expression of the platelet-derived growth factor receptor. The epidermal growth factor receptor is overexpressed in 60% of glioblastoma multiforme (GBM) and amplified in 40%. Both of these tyrosine kinase receptors signal to the mitogen activated Ras-RAF-MEK-ERK signaling pathway. RAF proteins are well known oncogenes, comprised by a family of three members: A-RAF, B-RAF and C-RAF. Especially B-RAF has been defined to be mutationally activated in a high percentage of melanomas, ovarial, thyroidal and colon carcinomas. C-RAF is discussed to be involved in lung cancer development. However, the role of Raf proteins during development of astrocytic tumors has only rarely been addressed in the literature. METHODS: The mutational status of A-RAF and B-RAF was assessed by sequencing in 66 and 44 human GBM, respectively. A panel of three normal brain samples, 15 LGA and 15 GBM was analyzed for gene amplification by dot blot hybridization, for mRNA expression by semiquantitative RT-PCR and for protein expression by Western blotting. The results were correlated with patients' prognosis. Finally, we performed functional assays using transient overexpression and siRNA mediated knock-down to address a putative function of A-RAF in glioma cell proliferation and migration. RESULTS: RAF mutations are rare events in GBM. No mutations were found in the A-RAF gene and only 2% of the tumors contained activating B-RAF mutations. A-RAF gene amplification could be detected more often. However, all three Raf proteins were overexpressed in astrocytic tumors. Both, A-RAF and C-RAF expression was negatively correlated with the patients' survival. In contrast, B-RAF expression had a positive effect. Neither A-RAF, nor C-RAF had any influence on proliferation or migration of GBM cells in functional assays. There are hints for an involvement of A-RAF in the regulation of the tumor cells metabolism and of C-RAF in angiogenesis. CONCLUSION: Raf proteins are clearly overexpressed in GBM and play a role during progression of these tumors. Therefore, the RAF-isoforms are possible candidates for small molecule therapies in conjunction with targeting parallel signaling cascades. However, initially specific functions of RAF during tumorigenesis of human gliomas have to be elucidated.